The interplay between board characteristics, financial performance, and risk management disclosure in the financial services sector: New empirical evidence from Europe - Gratiela Georgiana Noja; Eleftherios Thalassinos; Mirela Cristea; Irina Maria Grecu (Journal of Risk and Financial Management, 2021)
This paper empirically evidences the role played by board characteristics (skills, diversity, structure, independence) in supporting risk management disclosure and shaping the financial performance of European companies operating in the financial services sector. We exploit data selected from Thomson Reuters Eikon database in 2020 for the last fiscal year 2019 (FY0) on a longitudinal sample of 144 companies with the head offices in Europe (25 countries). Following an original empirical approach based on two modern financial econometric techniques, namely structural equation modelling (SEM) and network analysis through Gaussian graphical models (GGMs), the research endeavor outlines the decisive importance of an optimal board size, enhanced management skills, upward gender diversity (encompassed by women participation on board management), and structure (mainly a two-tier type, one management board, and a distinctive supervisory board) as fundamentals of risk management strategies, leading to improved financial achievements and a higher profitability for the analyzed companies.
Keywords: 330; financial performance; risk management; board characteristics; financial econometrics; financial services; strategy